Genome-wide transcriptome profiling reveals molecular response pathways of Trichoderma harzianum in response to salt stress - Yang, Qihong; Mao, Zhenchuan; Hao, Yali; Zheng, Shijie; Zhao, Jianlong; Li, Yan; Yang, Yuhong; Xie, Bingyan; Ling, Jian; Li, Yanlin (Frontiers in Microbiology, 2024)
Trichoderma harzianum exhibits a strong biological control effect on many important plant pathogens, such as Fusarium oxysporum, Botrytis cinerea, and Meloidogyne. However, its biocontrol effectiveness is weakened or reduced under salt stress. The aim of this study was to investigate the molecular response of T. harzianum to salt stress at the whole-genome level. Here, we present a 44.47 Mb near-complete genome assembly of the T. harzianum qt40003 strain for the first time, which was assembled de novo with 7.59 Gb Nanopore sequencing long reads (~170-fold) and 5.2 Gb Illumina short reads (~116-fold). The assembled qt40003 genome contains 12 contigs, with a contig N50 of 4.81 Mb, in which four of the 12 contigs were entirely reconstructed in a single chromosome from telomere to telomere. The qt40003 genome contains 4.27 Mb of repeat sequences and 12,238 protein-coding genes with a BUSCO completeness of 97.5%, indicating the high accuracy and completeness of our gene annotations. Genome-wide transcriptomic analysis was used to investigate gene expression changes related to salt stress in qt40003 at 0%, 2% (T2), and 4% (T4) sodium chloride concentrations. A total of 2937 and 3527 differentially expressed genes (DEGs) were obtained under T2 and T4 conditions, respectively. GO enrichment analysis showed that the T2-treatment DEGs were highly enriched in detoxification (P < 0.001), while the T4 DEGs were mainly enriched in cell components, mostly in cellular detoxification, cell surface, and cell wall. KEGG metabolic pathway analysis showed that 91 and 173 DEGs were significantly enriched in the T2 and T4 treatments, respectively (P < 0.01), mainly in the glutathione metabolism pathway. We further experimentally analyzed the differentially expressed glutathione transferase genes in the glutathione metabolic pathway, most of which were downregulated (13/15). In addition, we screened 13 genes related to active oxygen clearance, including six upregulated and seven downregulated genes, alongside five fungal hydrophobic proteins, of which two genes were highly expressed. Our study provides high-quality genome information for the use of T. harzianum for biological control and offers significant insights into the molecular responses of T. harzianum under salt-stress conditions.